2018
DOI: 10.3389/fpsyg.2018.01273
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Psychological Contract Breach and Employees’ Counterproductive Work Behaviors: The Mediating Effect of Organizational Cynicism and Work Alienation

Abstract: Psychological contract breach (PCB) may trigger negative attitudes in employees and ultimately cause further negative behaviors. By drawing on social exchange theory, this study aims to explore the link between PCB and counterproductive work behavior (CWB) by focusing on the mediating role of organizational cynicism and work alienation. We administered a cross-sectional survey of 484 energy company front-line employees. The conceptual model was examined via structural equation modeling. The results suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 116 publications
(142 reference statements)
11
76
0
5
Order By: Relevance
“…Numerous studies have been examined the association between psychological contract breach and counterproductive work behavior 64‐66 . Counterproductive work behavior is deliberately performed through the individuals to disrupt the discipline of the firm as well as damage the happiness of its associates 67 .…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have been examined the association between psychological contract breach and counterproductive work behavior 64‐66 . Counterproductive work behavior is deliberately performed through the individuals to disrupt the discipline of the firm as well as damage the happiness of its associates 67 .…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…Counterproductive work behavior is deliberately performed through the individuals to disrupt the discipline of the firm as well as damage the happiness of its associates 67 . According to social exchange theory, employees could answer to psychological contract breach with negative job attitudes, and these would make employees more prone to involve in counterproductive work behaviors, such as absence, withdrawal behaviors as well as deviant work behavior 64‐66 . Prior study has confirmed that psychological contract breach can activate absence and form anti‐citizenship behavior among employees 50,54 …”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…Empirical research has documented the positive association between PC breach and organizational cynicism (Chiaburu et al, 2013). However, most of these studies rely on either a global measure of cynicism (e.g., Li & Chen, 2018) or some of its subdimensions such as cognitive or affective cynicism (e.g., Johnson & O'Leary-Kelly, 2003), thereby not acknowledging its conceptual complexity. When investigating cynicism as a consequence of PC breach, using a global measure might obscure certain relationships as effect sizes might not be equal for each dimension.…”
Section: Organizational Cynicism and Social Exchangementioning
confidence: 99%
“…a) Workplace spirituality and WDB Workplace spirituality has recently been researched and associated with workplace deviance behavior [9]. Several researchers have shown that organizational cynicism leads to deviance behavior in the workplace [48], [49]. Other studies suggest that employees who have higher spirituality tend to avoid deviant actions in the workplace [22], [23].…”
Section: Workplace Spirituality Job Satisfaction and Workplace Deviamentioning
confidence: 99%